Internal Quality Assurance Program for ERBB2 (HER2) Testing Improves the Selection of Breast Cancer Patients for Treatment with Trastuzumab. (14th February 2012) - Martin, Vittoria; Camponovo, Antonella; Ghisletta, Morena; Bongiovanni, Massimo; Mazzucchelli, Luca
Abstract : International guidelines for ERBB2 (HER2) testing procedures in breast cancer patients highlight the importance of external quality control. In contrast, internal quality assurance programs have been poorly defined, and their clinical significance has not yet been investigated. We developed a quality assurance scheme by performing HER2 FISH on 724 patients randomly selected out of 1996 patients with breast cancer presenting at our institute. We collected samples monthly for tissue microarray analysis and correlated HER2 gene status with IHC scores. The concordance was excellent (κ = 0.92, P < 0.0001 ). HER2 amplification characterized 25% of score 2+ but also 13% of score 1+, thus expanding the number of patients eligible for trastuzumab. Based on these findings, the FISH test is now recommended at our institution for score 1+ and 2+ patients. Adherence to internal assurance program improves patient selection and may lead to the definition of in-house tailored diagnostic algorithms different from those proposed in international guidelines.